Blood rheology in lupus erythematosus. Issue 10 (October 1991) - Ernst, E; Hein, A; Meurer, M; Ruzicka, T
Abstract : Blood rheology is one of the determinants of perfusion and might therefore have an impact on the thromboembolic complications of lupus erythematosus. This study aimed at defining the flow properties of blood in patients with various types of lupus erythematosus. Results for 51 patients were compared with those for 20 controls matched for sex. The patients were divided into subgroups--chronic discoid, subacute cutaneous, and systemic lupus erythematosus--according to their clinical or laboratory characteristics. Blood and plasma viscosity, packed cell volume, red cell aggregation, and red cell deformability were used as parameters of blood rheology. Blood and plasma viscosity and red cell aggregation were significantly different in patients compared with controls, indicating reduced blood fluidity in lupus erythematosus. There were no marked sex differences. The rheological effects were greater in those with systemic lupus erythematosus than in those with chronic discoid or subacute cutaneous lupus erythematosus. The presence of a positive antinuclear antibody titre or methods of treatment (systemic steroids or retinoids) had no apparent effect on the parameters tested. It is suggested that a complex haemorheological deficit exists in lupus patients.